Soybean (Glycine max) Is Able to Absorb, Metabolize and Accumulate Fenbendazole in All Organs Including Beans - Podlipná, Radka; Navrátilová, Martina; Raisová Stuchlíková, Lucie; Moťková, Kateřina; Langhansová, Lenka; Skálová, Lenka; Szotáková, Barbora (International journal of molecular sciences, 2021)
Although manure is an important source of minerals and organic compounds it represents a certain risk of spreading the veterinary drugs in the farmland and their permeation to human food. We tested the uptake of the anthelmintic drug fenbendazole (FBZ) by soybean, a common crop plant, from the soil and its biotransformation and accumulation in different soybean organs, including beans. Soybeans were cultivated in vitro or grown in a greenhouse in pots. FBZ was extensively metabolized in roots of in vitro seedlings, where sixteen metabolites were identified, and less in leaves, where only two metabolites were found. The soybeans in greenhouse absorbed FBZ by roots and translocated it to the leaves, pods, and beans. In roots, leaves, and pods two metabolites were identified. In beans, FBZ and one metabolite was found. FBZ exposure did not affect the plant fitness or yield, but reduced activities of some antioxidant enzymes and isoflavonoids content in the beans. In conclusion, manure or biosolids containing FBZ and its metabolites represent a significant risk of these pharmaceuticals entering food consumed by humans or animal feed. In addition, the presence of these drugs in plants can affect plant metabolism, including the production of isoflavonoids.
Keywords: fenbendazol; Fenbendazole; anthelmintics; isoflavonoids; benzimidazoles; pharmaceuticals; Glycine max; biologický transport; Biotransformation; biotransformace; antioxidant enzymes; biotransformation; Biological Transport